ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-EFFICACY SISWA SEKOLAH MENENGAH PERTAMA - Resmiati, Tati; Hamdan, Hamdan (IKIP Siliwangi, 2019)
Problem solving is one of the basic abilities in mathematics learning. Problem solving skills can encourage students to think critically, creatively, and can develop other mathematical abilities. The research conducted aims to analyze students 'problem solving abilities in solving problems in mathematical problems and to determine students' self-efficacy towards mathematics. The approach used is a qualitative descriptive approach. The test given is a description problem and attitude scale to measure students' self-efficacy. Questions were tested on class VIII students in one of the junior high schools in the city of Bandung. The results of the study showed that as many as 1 student could not identify the adequacy of the data to solve the problem so that he got a score of 0, while 21 students were not precise in understanding the problem given, while 7 students could not complete the mathematical model and could not verify the correct solution, so it can be stated that the problem solving abilities of students in one of the junior high schools in Bandung are still low so that efforts need to be made to improve, but students have good self-efficacy in mathematics.